2006
DOI: 10.1074/jbc.m511640200
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Remodeling and Transcriptional Activity of the Bone-specific Osteocalcin Gene Require CCAAT/Enhancer-binding Protein β-dependent Recruitment of SWI/SNF Activity

Abstract: Tissue-specific activation of the osteocalcin (OC) gene is associated with changes in chromatin structure at the promoter region. Two nuclease-hypersensitive sites span the key regulatory elements that control basal tissue-specific and vitamin D 3 -enhanced OC gene transcription. To gain understanding of the molecular mechanisms involved in chromatin remodeling of the OC gene, we have examined the requirement for SWI/SNF activity. We inducibly expressed an ATPase-defective BRG1 catalytic subunit that forms ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
102
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 42 publications
11
102
0
Order By: Relevance
“…Interestingly, BMP-2 has been shown to increase binding of Osx to Ibsp or osteocalcin promoters with a concomitant decrease of NO66 binding and activity (15). Similarly, BMPs increase the expression and function of the ATPdependent chromatin-remodeling complex SWI/SNF, which has been shown to be absolutely essential for osteogenesis, especially the complexes containing Brg1 as a catalytic core (53)(54)(55). Our study demonstrates that Osx is able to increase recruitment of p300 and Brg1 to the promoters of its target genes Fmod and Ibsp in vivo and that Osx directly associates to these cofactors through protein-protein interactions that are further enhanced by BMP signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BMP-2 has been shown to increase binding of Osx to Ibsp or osteocalcin promoters with a concomitant decrease of NO66 binding and activity (15). Similarly, BMPs increase the expression and function of the ATPdependent chromatin-remodeling complex SWI/SNF, which has been shown to be absolutely essential for osteogenesis, especially the complexes containing Brg1 as a catalytic core (53)(54)(55). Our study demonstrates that Osx is able to increase recruitment of p300 and Brg1 to the promoters of its target genes Fmod and Ibsp in vivo and that Osx directly associates to these cofactors through protein-protein interactions that are further enhanced by BMP signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that in addition to the canonical interactions, several mechanisms of C/EBP-induced gene transcription have been demonstrated including interplays with other transcription factors such as (NF-kB, AP-1, Sp1, CREB) [37][38][39][40] or recruitment of various transcriptional co-regulators that affect chromatin conformation, a condition that untimely facilitates the trapping of basal transcription factors. [41,42] Based on that fact that NF-kB and AP-1 are direct regulators of ET-1 transcription, the existence of non-canonical associations among transcriptional complexes formed by heterodimers consisting of C/EBP and other transcription factors that might or might not contain the basicleucine zipper domain [18] should be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…BRG1 has been shown to direct different cellular processes by recruitment to cis elements through divergent transcription factors including hormone receptors, the erythroid factors erythroid Krüppel-like factor and GATA-1 (which activate the ␤-globin gene) and C/EBP␤ (16,17,42,43). Similar to our findings related to the regulation of Cyp24a1 transcription, C/EBP␤ has been reported to recruit and cooperate with BRG1 to regulate the expression of myeloid genes (15), the osteocalcin gene in osteoblastic cells (16), and the mammary tissue-specific ␤-and ␥-casein genes (17).…”
Section: Discussionmentioning
confidence: 99%
“…In additional studies in COS-7 cells, suboptimal 1,25(OH) 2 Previous studies from our laboratory showed that C/EBP␤ is induced by 1,25(OH) 2 D 3 in kidney and osteoblastic cells and is a potent enhancer of VDR-mediated Cyp24a1 transcription (26). C/EBP␤ has also been reported to recruit the SWI/SNF complex to regulate cell type-specific genes (15)(16)(17). Hence, we next investigated the role of BRG1 in the C/EBP␤ enhancement of 1,25(OH) 2 D 3 -induced Cyp24a1 transcription.…”
Section: Brg1-containing Swi/snf Complex Vdr and C/ebp␤ Cooperate Imentioning
confidence: 99%
See 1 more Smart Citation